2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32019
|View full text |Cite
|
Sign up to set email alerts
|

A Writing in the Disciplines Approach to Technical Report Writing in Chemical Engineering Laboratory Courses

Abstract: Catherine (Cat) Hubka, MFA, holds dual appointments at the University of New Mexico in the Departments of Chemical and Biological Engineering (CBE) and Department of English. For CBE, she is embedded in the 300 and 400 labs where she supports curriculum redesign focused on incorporating contentbased writing approaches. In the Department of English, Cat teaches in the Core Writing Program where her pedagogy incorporates creative writing workshops and collaborative writing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…52 Embedding the process of writing in a laboratory setting provided a structured opportunity for students to review their own and others' work critically, thus being guided towards improving their technical writing. 53 Jocuns and Stevens proposed a 'trajectory of identification' in the ability of engineering students to 'talk http://www.td-sa.net Open Access engineering', 49 arguing that spoken technical communication was a significant part of the development of an engineering student's identity. Presentation skills, particularly in laboratory demonstrations, were identified as a key oral communication genre in engineering, entailing the development of a 'socioscientific argumentation [that] includes the application of moral and ethical values and personal identity'.…”
Section: Communicating Engineering Identities: Discursive Practices In the Laboratorymentioning
confidence: 99%
“…52 Embedding the process of writing in a laboratory setting provided a structured opportunity for students to review their own and others' work critically, thus being guided towards improving their technical writing. 53 Jocuns and Stevens proposed a 'trajectory of identification' in the ability of engineering students to 'talk http://www.td-sa.net Open Access engineering', 49 arguing that spoken technical communication was a significant part of the development of an engineering student's identity. Presentation skills, particularly in laboratory demonstrations, were identified as a key oral communication genre in engineering, entailing the development of a 'socioscientific argumentation [that] includes the application of moral and ethical values and personal identity'.…”
Section: Communicating Engineering Identities: Discursive Practices In the Laboratorymentioning
confidence: 99%
“…We also learned the importance of not making it easy for students to just "accept all" changes, instead focusing on modeling just a few changes and asking students to make the edits themselves. We found that faculty had ideas of various ways to implement these ideas, from using peer-reviews to component submission, yet all of these variants supported student growth, both in terms of conceptual learning and as technical writers, provided the students had to make revisions [52,53].…”
Section: Offer Limited But Specific Feedback On Writing and Require R...mentioning
confidence: 99%
“…To produce engineering graduates with the communication skills necessary to be successful in the modern workforce, engineering curriculums need to improve how communication skills are taught. The movement towards more effective teaching of communication skills to engineers has resulted in opportunity for collaboration with communication experts [3,4] and the launching of Writing Across the Curriculum (WAC) or Writing in the Disciplines (WID) programs [5][6][7].…”
Section: Introductionmentioning
confidence: 99%